CAUSALITY OF TOURISM INCOME, FOREIGN DIRECT INVESTMENT AND ECONOMIC GROWTH IN INDONESIA - Muhammad Habibur Rohman; Suyanto Suyanto; Firman Rosjadi (Riset Ekonomi Pembangunan, 2021)
Tourism sector and foreign direct investment in Indonesia are currently in a strategic position that receives a major attention from national as well as international parties. Tourism income and foreign direct investment inflows are largely believed to contribute greatly to the government income, thus increases economic growth of a country. However, the empirical findings on Indonesia are mixed. This current study contributes to the debate in the empirical literature by investigate the short-term and long-term relationship and the direction of causality between international tourism income, foreign direct investment and economic growth in Indonesia from 1995 to 2018. It provides insight into the literature by examining the national level data. Granger causality test is applied. The interesting finding is that foreign direct investment causes the increase in tourism income and the increase in the economic growth. The reverse is also applies that the tourism income attract foreign direct investment and spur economic growth. These findings support the efforts of the government, business players, and local society in promoting tourism sector in attracting foreign investment as well as promoting economic growth.